Čerpání finančních prostředků z fondů EU - Herůfek, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce se zabývá možností čerpání finančních prostředků z Evropské unie. Obsahuje teoretické poznatky z oblasti strukturálních fondů Evropské unie, analýzu současného stavu sledované společnosti a v návrhové části vypracování projektové žádosti spolu s její ekonomickou analýzu.

Master´s Thesis is concerned about possibility of receiving funding from European union. It contains theoretical background about structural funds of European union, analysis of the present circumstances of the company and, in the proposal part of the thesis, there is executed design of application within the economic analysis.
Receiving Funding from EU Funds
Keywords: Evropské dotace; čerpání financí z Evropské unie; ekonomická efektivita investice; European subsidies; receiving funding from EU funds; economic effect of the investment